Editorial. Issue 1 (1st March 2023) - Powell, Bryan; Smith, Gareth Dylan
In this introduction, the journal editors, Gareth Dylan Smith and Bryan Powell, pay tribute to Jarritt Sheel, a colleague whose light shone brightly in the field of popular music education until he died suddenly in late 2022. Next, the editors reflect briefly on the previous, sixth volume of the Journal of Popular Music Education, which featured two guest-edited Special Issues – one on music and the family, and another on women and popular music – and a general issue. The editors then provide a summary overview of the articles in this issue of the journal, by Ethan Hein, Natasha Hendry, Esther Morgan-Ellis, Aidan Harvey, Bryan Powell, Jonathan Kladder and Ian Cummings, and a book review by Jonathan Dillon.